PENGARUH LIVE SHOPPING, DISCOUNT, DAN KUALITAS PRODUK TERHADAP IMPULSE BUYING PADA MARKETPLACE TIKTOK SHOP - Aulia Asmarani; Murti Wijayanti; Dody Kurniawan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The aim of this research is to find out whether live shopping, discounts and product quality have an effect on impulse buying among students of the Bhayangkara University Management Study Program, Jakarta Raya Class of 2020. This type of research is quantitative and the data analysis used is the classical assumption test and multiple linear regression analysis, to test and prove the research hypothesis using the SPSS version 26 application. There were 154 respondents in this research population. Bhayangkara University, Jakarta Raya is the subject of this research. The research results show that: 1) partially live shopping has a significant and positive effect on impulse buying, with tcount of 3.129 > ttable 1.975 with a significance level of 0.002 < 0.05. 2) partially discounts have a significant and positive effect on impulse buying, with tcount of 3.030 > ttable 1.975 with a significance level of 0.003 < 0.05. 3) partially product quality has a significant and positive effect on impulse buying, with tcount of 3.158 > ttable 1.975 with a significance level of 0.002 < 0.05. 4) live shopping, discounts and product quality have a simultaneous and significant effect on impulse buying, seen from fcount 98.796 > ftable 2.66, where 0.000 < 0.05 is the significance value.